"Empathizing" with Machines. Issue 1 (24th January 2019) - BUTLER, CHRIS
Abstract : When we study human systems and organizations we have a job that requires to empathize or at the very least be compassionate towards the experiences others are having. This allows to understand their goals, problems, and how we can best make their lives better. When machines start to do things that we can't imagine how do we continue to work with them? What is necessary to create great combinations of humans and machines? What is a machine's purpose? Very simply: it is to serve human purposes. As technology continues to build facades that hide the human element we need to pull back the curtain (like the one in the Wizard of Oz) and see that the tools we build are really us reflected back. We have the choice to make tools that are good or bad for us.